Quantitative methods for business decisions - Curwin, Jon. (International Thomson Business Press, 1996)
This book is divided into seven parts: Quantitative information; Descriptive statistics; Measuring uncertainty; Statistical inference; Relating variables and predicting outcomes; Modelling; and Mathematical background.